Torture garden - Bloch, Robert, 1917-1994; Rosenberg, Max J., 1914-2004; Subotsky, Milton; Francis, Freddie, 1917-2007; Palance, Jack, 1919-2006; Meredith, Burgess, 1907-1997; Adams, Beverly; Cushing, Peter, 1913-1994; Denham, Maurice, 1909-2002 (Columbia Pictures ; Sony Pictures Home Entertainment, 2005)
"A special sideshow torture exhibit has the power, according to showman, Dr. Diablo, to warn people of evil in their futures."--Container.